Elective caesarean section on maternal request in Germany: factors affecting decision making concerning mode of delivery - Stützer, Paul Philipp; Berlit, Sebastian; Schmahl, Christian; Sütterlin, Marc; Tuschy, Benjamin (Archives of gynecology and obstetrics, 2017)
Purpose: To investigate sociopsychological factors of women undergoing a caesarean section on maternal request (CSMR). Methods: Twenty-eight women who underwent CSMR and 29 women with vaginal delivery (VD) filled in standardized questionnaires concerning psychological burden (SCL-R 90), fear of childbirth (W-DEQ, STAI), personality structure (HEXACO-Pi-R) and social support (F-SozU) as well as one questionnaire assessing potential factors influencing their mode of delivery. Results: Women with CSMR were older (36.5 ± 5.4 vs. 30.6 ± 5.2 years; p < 0.001) and suffered more from fear of childbirth (W-DEQ 4.3 ± 0.8 vs. 3.7 ± 1.2; p = 0.041), concerns for their child (W-DEQ 2.0 ± 1.5 vs. 1.3 ± 0.7; p = 0.026) and appraised the birth less negative (W-DEQ 2.0 ± 0.7 vs. 2.7 ± 1.1; p = 0.008). The majority of parturients had chosen their preferred mode of delivery before pregnancy (CS 61% vs. VD 82%, p = 0.328). In the decision-making process for the mode of delivery, the advice of the partner (85 and 90%) played an important role. 82% of the women who delivered via CSMR did not regret the decision for this mode of delivery. Conclusion: Women who underwent CS had higher fear of childbirth and appraised the birth less negative. The majority did not regret the decision for the CS and would even choose this mode of delivery for their next pregnancy. Although the partner and the physician seem to be important in the decision process for of the mode of delivery, reasons for the choice for CSMR appear to be multifactorial.